2010
DOI: 10.1007/s10803-010-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Social Skill Development in Children With Pervasive Developmental Disorders: A Feasibility and Efficacy Study

Abstract: A randomized controlled design was employed to evaluate a social skills intervention for children with pervasive developmental disorders. Aims included evaluating the acceptability of the program and gathering preliminary evidence on efficacy. Forty-four children, ages 8-11 years, were randomly assigned to treatment or wait list. Treatment consisted of a 16-week group intervention designed to teach appropriate social behavior. Between group comparisons showed that children in treatment were rated as improved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 45 publications
1
86
0
8
Order By: Relevance
“…The participants were children between the ages of 7 and 12 years, with the exception of one trial that included adolescents between the ages of 13 and 17 years (47). To some extent, the outcome measures differed between the trials: 4 trials measured social competency (47)(48)(49)(50), and 2 trials measured friendship quality (48,51). The social skills groups improved in overall social competence (effect size = 0.47; 95% confidence interval, 0.16 to 0.78) and friendship quality (effect size = 0.41; 95% confidence interval, 0.02 to 0.81), but there was no effect on emotional recognition and understanding of idioms.…”
Section: Social Skills Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were children between the ages of 7 and 12 years, with the exception of one trial that included adolescents between the ages of 13 and 17 years (47). To some extent, the outcome measures differed between the trials: 4 trials measured social competency (47)(48)(49)(50), and 2 trials measured friendship quality (48,51). The social skills groups improved in overall social competence (effect size = 0.47; 95% confidence interval, 0.16 to 0.78) and friendship quality (effect size = 0.41; 95% confidence interval, 0.02 to 0.81), but there was no effect on emotional recognition and understanding of idioms.…”
Section: Social Skills Trainingmentioning
confidence: 99%
“…The Diagnostic Analysis of Nonverbal Accuracy (60), which measures an individual's ability to recognize facial expressions, was used in two studies (50,51). In 2 other studies, the improvement subscale of the Clinical Global Impressions Scale (61) was used by blinded investigators (49,57). Four of the trials were determined to have a high risk of bias, mainly as a result of uncertainties related to missing information (51,(55)(56)(57).…”
Section: Social Skills Trainingmentioning
confidence: 99%
“…The lack of prosodic communication and expressive gestures is evident along with fl at affect and impaired awareness of social contexts. These behaviors are often misinterpreted as evidence of depression (Koenig et al, 2010 ;Lane, Young, Baker, & Angley, 2010 ).…”
Section: Focus On Behavioral Characteristicsmentioning
confidence: 99%
“…Asperger syndrome students have more diffi culty communicating with peers than with adults. And they have more diffi culty communicating with peers and adults than do "typical" comparison groups (Koning & Magill-Evans, 2001 ;Koenig et al, 2010 ;Lasgaard et al, 2010 ).…”
Section: Communicationmentioning
confidence: 99%
“…The most common psychosocial treatment for HFASD is social skills groups (Reichow, Steiner, & Volkmar, 2012;Reichow & Volkmar, 2010). These groups target development of social competencies (e.g., social skills/behaviors, social understanding and knowledge, etc., Kaat & Lecavalier, 2014) using techniques including direct instruction, modeling, role-play/rehearsal, repeated practice, performance feedback, and reinforcement, and some include parent training (Koenig et al, 2010;Reichow et al, 2012;White, Koenig, & Scahill, 2007). Recent reviews by Reichow and Volkmar (2010) and Reichow et al (2012) concluded that social skills groups were a promising treatment approach for increasing social skills/competence, particularly for school-age youth with HFASD.…”
mentioning
confidence: 99%